Given-New Effects on the Duration of Gestures and of Words in Face-to-Face Dialogue. Issue 8 (14th September 2022) - Holler, Judith; Bavelas, Janet; Woods, Jonathan; Geiger, Mareike; Simons, Lauren
ABSTRACT: The given-new contract entails that speakers must distinguish for their addressee whether references are new or already part of their dialogue. Past research had found that, in a monologue to a listener, speakers shortened repeated words. However, the notion of the given-new contract is inherently dialogic, with an addressee and the availability of co-speech gestures. Here, two face-to-face dialogue experiments tested whether gesture duration also follows the given-new contract. In Experiment 1, four experimental sequences confirmed that when speakers repeated their gestures, they shortened the duration significantly. Experiment 2 replicated the effect with spontaneous gestures in a different task. This experiment also extended earlier results with words, confirming that speakers shortened their repeated words significantly in a multimodal dialogue setting, the basic form of language use. Because words and gestures were not necessarily redundant, these results offer another instance in which gestures and words independently serve pragmatic requirements of dialogue.